2016
DOI: 10.5026/jgeography.125.699
|View full text |Cite
|
Sign up to set email alerts
|

Land Classification and Flood Characteristics of the Pampanga River Basin, Central Luzon, Philippines

Abstract: The Pampanga River basin, which is the second largest drainage basin on Luzon Island (Republic of the Philippines) , frequently suffers from severe flood events, caused by monsoon rainfall and typhoon strikes. Therefore, the aim of this study is to determine local flood characteristics and potential flood vulnerability, based on the basin's geography (e.g., distribution of topography, land use and past flood records) . Our land classification shows that the basin consists of three major topographic regions: mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Land subsidence is a signi cant problem affecting rice lands in the Philippines, especially in areas surrounding Metro Manila, such as Bulacan, Pampanga, and Nueva Ecija (Espiritu et al, 2022;Rodolfo & Siringan, 2006). One major reason for this subsidence is groundwater over-extraction (Nagumo & Sawano, 2016). This leads to a quick fall of the water table and compaction of the aquifer systems, with annual subsidence average of about 2.5 cm and maximum 4 cm.…”
Section: Land Subsidence Threatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Land subsidence is a signi cant problem affecting rice lands in the Philippines, especially in areas surrounding Metro Manila, such as Bulacan, Pampanga, and Nueva Ecija (Espiritu et al, 2022;Rodolfo & Siringan, 2006). One major reason for this subsidence is groundwater over-extraction (Nagumo & Sawano, 2016). This leads to a quick fall of the water table and compaction of the aquifer systems, with annual subsidence average of about 2.5 cm and maximum 4 cm.…”
Section: Land Subsidence Threatsmentioning
confidence: 99%
“…This land subsidence affects rice production in several key ways. First, it reduces the drainage capacity of rivers and increases ooding in low-lying agricultural areas (Nagumo & Sawano, 2016). Prolonged ooding damages rice crops and makes it di cult to plant and harvest rice.…”
Section: Land Subsidence Threatsmentioning
confidence: 99%
“…The region is susceptible to recurrent flooding, particularly during the rainy seasons, owing to its classification as an alluvial plain, with a portion of it transformed into a swamp. These floods primarily result from the overflow of the Pampanga River, causing water to accumulate and impede efficient drainage, leading to severe floods [31]. In an inter-view with the Candaba Municipal Agricultural Officer, it was revealed that a damage report on agriculture reaching 20% and above should be initially reported to the local officials of the Disaster Risk Reduction and Management Office (DRRMO).…”
Section: Study Sitesmentioning
confidence: 99%